STUDENTS’ PERCEPTIONS ON A MULTIMODAL DIGITAL STORYTELLING BOOK USE IN A WRITING CLASS DURING COVID-19 PANDEMIC - Zuhriyah, Mukminatus (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2023)
This study aimed to describe the students’ perceptions toward the use of a multimodal digital storytelling book in the writing class during COVID-19 pandemic. This research used a descriptive qualitative design. Meanwhile, the participants of this study were twenty students in the second semester of an English language education department in a private university located in East Java. The data were collected through the closed-ended questionnaires which were shared through Google Form. These questionnaires consisted of seven statements related to the use of a multimodal digital storytelling book in their writing class. After all the data were collected, then, the data were tabulated and calculated its frequency for each questionnaire item. The results of questionnaire analysis revealed that more than 85% of the students gave positive perceptions toward the use of a multimodal digital storytelling book in their writing class. Hopefully, the results of this study can become a reference for English teachers especially and language teachers generally when they teach writing online.